2007
DOI: 10.4081/ijas.2007.1s.488
|View full text |Cite
|
Sign up to set email alerts
|

The effect of melatonin on bovinein vitroembryo development

Abstract: The aim of the present study was to evaluate the effect of melatonin supplementation during in vitro maturation on fertilization and embryo development in cattle. Bovine cumulus-oocyte-complexes (COC), recovered from abattoir ovaries, were matured in vitro in the absence (control) and in the presence of 10 μM, 100 μM and 1 mM of melatonin. Matured oocytes were fertilized in vitro with frozen-thawed sperm and cultured up to the blastocyst stage. The results of this work demonstrated that melatonin enrichm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 5 publications
2
10
0
4
Order By: Relevance
“…Melatonin during IVM increases the nuclear maturation and blastocyst rates in porcine (Kang et al, 2009) and in buffalo (Manjunatha et al, 2009). On the other hand, in agreement with our results, Tsantarioutou et al (2007) observed no differences on bovine cleavage and blastocyst rates when melatonin was added to IVM medium. Those authors did not study the nuclear maturation rate.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Melatonin during IVM increases the nuclear maturation and blastocyst rates in porcine (Kang et al, 2009) and in buffalo (Manjunatha et al, 2009). On the other hand, in agreement with our results, Tsantarioutou et al (2007) observed no differences on bovine cleavage and blastocyst rates when melatonin was added to IVM medium. Those authors did not study the nuclear maturation rate.…”
Section: Resultssupporting
confidence: 82%
“…The protective role of free radical scavengers in maturation culture medium has been documented (Tsantarioutou et al, 2007;Kang et al, 2009;Manjunatha et al, 2009). Melatonin acts as a potent scavenger of free radicals (Tan et al, 2007) and a direct gonadal response to melatonin has been also reported, including stimulation of progesterone (Adriaens et al, 2006) and estradiol synthesis (Sirotkin and Schaeffer, 1997), and improvement of oocyte quality and maturation (Chattorag et al, 2005;Kang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…() and Tsantarliotou et al. () tested the melatonin effect with different treatment strategies and did not find any consequence on the development rates of the in vitro ‐produced bovine embryos. Recently, Takada et al.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our results, Papis et al (2007) and Tsantarliotou et al (2010) 2009), pig (Choi et al, 2008;Kang et al, 2009;Shi et al, 2009) andmice (Ishizuka et al, 2000).…”
Section: Discussionsupporting
confidence: 81%